Foreign Exchange Order Flow as a Risk Factor - Burnside, Craig; Cerrato, Mario; Zhang, Zhekai (Journal of Financial and Quantitative Analysis, 2025)
Abstract We propose a novel pricing factor for currency returns motivated by the market microstructure literature. Our factor aggregates order flow data to provide a measure of buying and selling pressure related to conventional currency trading strategies. It successfully prices the cross-section of currency returns sorted on the basis of forward discount and momentum. The association between our factor and currency returns differs according to the customer segment of the foreign exchange market. In particular, it appears that financial customers are risk-takers in the market, while nonfinancial customers serve as liquidity providers.